The Potential Therapeutic Role of Beta-Caryophyllene as a Chemosensitizer and an Inhibitor of Angiogenesis in Cancer - Emad A. Ahmed (Molecules)
The natural, highly lipophilic bicyclic sesquiterpenes, Beta-Caryophyllene (BCP), was highlighted in several recent preclinical studies to enhance chemo-sensitization in chemo-resistant tumors and to efficiently inhibit angiogenesis and cancer cells’ ability to invade and metastasize. Previous studies have researched the reasons for the synergistic effect of Beta-Caryophyllene in combination therapy and its role as a chemosensitizer and an inhibitor of angiogenesis through investigating the involved mechanisms and signaling molecules. These include the lipophilic nature of BCP, the selective interaction of BCP with CB2, the binding affinity of BCP to the receptor binding sites at the angiogenic vascular endothelial growth factor, and the upstream effect on JAK1/STAT3 pathway and other signaling pathways. Herein, the BCP role in enhancing chemo-sensitization of chemo-resistant tumors and in inhibiting angiogenesis and cancer cells’ ability to invade and metastasize are highlighted. Beta-Caryophyllene appears to be a promising candidate in treating cancer when co-supplemented with drugs such as cisplatin, gemcitabine and sorafenib. Clinical trials are needed to validate the potential therapeutic effect of BCP as a co-supplementary drug in cancer therapy, helping to sensitize cancer response to drugs, modulating signaling pathways, and lowering the drugs’ doses besides working as anti-angiogenetic drug.